log2 + 2logx = log(4x-2)
log2 + log(x^2) = log(4x-2) ....... since a*log b = log(b^a)
log[2*(x^2)] = log(4x-2) ........ since log a + log b = log a*b
2*(x^2) = 4x - 2
x^2 = 2*x - 1
x^2 - 2*x +1 = 0
(x - 1)^2 = 0
Two equal roots: x=1,1
Thus, x = 1
2007-01-03 02:06:51
·
answer #1
·
answered by Som™ 6
·
1⤊
0⤋
log2 + 2logx = log(4x-2) log2 + logx^2 = log(4x-2) log(2x^2) = log(4x-2) 2x^2 = 4x-2 2x^2 - 4x + 2 = 0 2(x^2 - 2x + 1) = 0 2(x-1)(x-1) = 0 x = 1
2016-05-22 22:43:32
·
answer #2
·
answered by Anonymous
·
0⤊
0⤋
log2 + 2logx = log(4x-2)
log2 + log(x^2) = log(4x-2)
log[2*(x^2)] = log(4x-2)
2*(x^2) = 4x - 2
Dividing both sides by 2
x^2 = 2*x - 1
x^2 -2x +1 = 0
x^2 -2.x.1 +1^2 = 0
(x - 1)^2 = 0
(x - 1)(x - 1) = 0
(x - 1) = 0, (x - 1) = 0
x = 1, 1
2007-01-03 02:13:44
·
answer #3
·
answered by Sheen 4
·
0⤊
0⤋
log2+2logx=log(4x-2)
log2+log(x^2)=log(4x-2)
{2x^2/(4x-2)}=0
2x^2=4x-2
2x^2-4x+2=0
x^2-2x+1=0
(x-1)^2=0
So, x=1
2007-01-03 03:25:25
·
answer #4
·
answered by sugan 1
·
0⤊
0⤋
here is the solution:
=>Log2 + 2log x=log(4x-2)
=>Log2 +logx2=log(4x-2) //by the property of log
=>2 * x2 =4x – 2
=>2 x2 – 4x +2=0
=>x2 – 2x +1 =0
=>(x-1)2=0
=>x = 1,1
2007-01-03 02:23:26
·
answer #5
·
answered by Anonymous
·
0⤊
0⤋
log2 + 2logx = log(4x-2)
log 2x^2=log (4x-2)
2x^2=4x-2
x^2-2x+1=0
(x-1)^2
2007-01-03 03:45:10
·
answer #6
·
answered by yupchagee 7
·
0⤊
0⤋
2 log x = log x²
log 2 + log x² = log 2x²
So log (2x²) = log (4x-2)
2x² = 4x-2
=> 2x² - 4x + 2 = 0
=> x² - 2x + 1 = 0
so x = 1 (1 is a double root)
2007-01-03 02:11:47
·
answer #7
·
answered by anton3s 3
·
0⤊
0⤋
x=56
2007-01-03 02:10:30
·
answer #8
·
answered by Anonymous
·
0⤊
0⤋
log2x^2=log(4x-2)
2x^2=4x-2
2x^2-4x+2=0
dividing by2
x^2-2x+1=0
(x-1)^2=0
x=1,1
2007-01-03 02:09:37
·
answer #9
·
answered by raj 7
·
0⤊
0⤋
Hey I came up with x=2.... lemme know if I am right... i dont even know for real if I am ..... but hopefully I am!
2007-01-03 02:09:38
·
answer #10
·
answered by Get_in_my_belly 3
·
0⤊
0⤋